Surface structure evolution in a homologous series of ionic liquids - Haddad, Julia; Pontoni, Diego; Murphy, Bridget M.; Festersen, Sven; Runge, Benjamin; Magnussen, Olaf M.; Steinrück, Hans-Georg; Reichert, Harald; Ocko, Benjamin M.; Deutsch, Moshe (Proceedings of the National Academy of Sciences)
Interfaces of room temperature ionic liquids (RTILs) are important for both applications and basic science and are therefore intensely studied. However, the evolution of their interface structure with the cation’s alkyl chain length n from Coulomb to van der Waals interaction domination has not yet been studied for even a single broad homologous RTIL series. We present here such a study of the liquid–air interface for n=2to 22 , using angstrom-resolution X-ray methods. For n<6 , a typical “simple liquid” monotonic surface-normal electron density profile ρe(z) is obtained, like those of water and organic solvents. For n>6 , increasingly more pronounced nanoscale self-segregation of the molecules’ charged moieties and apolar chains yields surface layering with alternating regions of headgroups and chains. The layering decays into the bulk over a few, to a few tens, of nanometers. The layering periods and decay lengths, their linear n dependence, and slopes are discussed within two models, one with partial-chain interdigitation and the other with liquid-like chains. No surface-parallel long-range order is found within the surface layer. For n=22 , a different surface phase is observed above melting. Our results also impact general liquid-phase issues like supramolecular self-aggregation and bulk–surface structure relations.